Organized by Re-Engineering Approach and its Relationship with Organizational Innovation at the Melli Bank of Zabol - Mohammad Ghasemi (Journal of Global Pharma Technology, 2017)
The current era's organizations confront with numerous issues and challenges such as quick, instantaneous and unpredictable changes, special orders and different tastes of customers. Therefore organizations have taken different forms and will embark on the changes to survive and preserve their positions. Examining the literature of reengineering and organizational innovation, explanation of the relation between organizing and reengineering of organizational innovation approach as the main target and in addition auxiliary targets such as explanation of the relation between the fivefold dimensions of reengineering of organizational innovation improvement and explanation of the relation of each of these dimensions with the threefold dimensions of organizational innovation are examined in this study. The method of the research is descriptive and of correlation type. The statistical society of the research is all the staff of Melli bank of Zabol. In order to determine the sample volume, Morgan table was used. Collected data are analyzed using the standard questionnaires of reengineering and organizational innovation, statistical test and SPSS software. Validity of the questionnaires was confirmed by professors and experts and their reliability was confirmed through Cronbach's alpha. The results obtained from the tests and research tool indicate a meaningful relation between the two variables. The main hypothesis stating that implementation of reengineering approach and organizational innovation improvement have a meaningful relation with each other was confirmed with a correlation coefficient of 0.961 and an error of less than 0.05 together with auxiliary hypotheses. Keywords: Reengineering, Organizational Innovation, Melli Bank, Redesign Of Business Processes, BPR.